Absence of Hepatitis B Resistance Mutants before Introduction of Oral Antiviral Therapy. (12th September 2013) - Moehlen, Martin; De Medina, Maria; Hill, Mary; Jeffers, Lennox; Schiff, Eugene R.; Martin, Paul
Abstract : Introduction . The aim of this study was to assess whether hepatitis B virus drug resistant mutations antedated the widespread use of nucleos(t)ide analogues in treatment naïve patients. A number of reports have suggested that drug resistant mutants can be detected in apparently treatment naïve patients. Study . Fifty deidentified serum samples collected from 1986 to 1992 from patients with replicative chronic HBV infection at the University of Miami were genotyped and tested for resistance mutations using a line probe assay InnoLiPA HBV DR v2/v3. Serum HBV DNA was measured. All patients had documented chronic HBV infection with a detectable viral load, HBeAg seropositivity, and absence of HIV infection. Results . Of the 50 individuals included, 86% were male, mean age was 40 ± 12 years, and mostly genotype A. The mean HBV DNA was 126 pg/mL (range 6.4 to 557.0). No mutations were identified. Conclusions. The absence of drug induced mutations in these sera collected several years prior to the introduction of oral antiviral therapy suggests that these mutations do not occur in treatment naïve populations. Detection of drug resistance in an apparently treatment naïve subject suggests either unrecognized prior antiviral therapy or infection by an inoculum from a treatment experienced patient.